THE ROLE OF READING ANXIETY AND ANOMIE IN EXAMINATION MISCONDUCTS IN NIGERIAN HIGHER EDUCATION - Ruth Abraham, Dienye (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
Dishonesty in examinations has always plagued Nigeria's academic system. This affects all levels of education, from primary to tertiary level. Numerous studies have underscored the contributory factors in examination misconduct in academia. However, little is known about the role of socio-psychological variables like reading anxiety and anomie. The present study examined reading anxiety and anomie as predictors of examination misconduct in higher education in Nigeria. Two hundred and forty-eight students, 118 males and 130 females aged 18 to 30 (M = 21.4, SD = 1.92) were conveniently pooled from tertiary institutions in River state, Nigeria, as the participants. A self-report questionnaire was used for data collection. A cross-sectional survey design was adopted for the study. Data from the respondents were analyzed using the statistical package for social sciences (SPSS, v23). A multiple regression analysis indicated that the predictors (reading anxiety and anomie) significantly predicted examination misconduct in higher education F (1,246), 36.52, P<.000. Most importantly, the R2 indicated that the predictor variables contributed to about 45.6% of the variance in examination misconduct among the respondents. The result has implications for curbing the menace of examination misconduct in academia.